The Perceived Social Stigma of People with Epilepsy with regard to the Question of Employability - Jéssica Lopes de Souza; Aline Scardoeli Faiola; Carmen Silvia Molleis Galego Miziara; Maria Luiza Giraldes de Manreza (Neurology Research International)
Objective. To evaluate the perceived social stigma of people with epilepsy with regard to the question of employability. Methods. A structured questionnaire was given to two groups of people with chronic diseases: those with epilepsy (study group) and those with heart disease (control group). The questions concerned employability. Results. Having epilepsy was more strongly associated with higher unemployment rates (p<0.0001); job layoffs (p=0.001); being unfit to work (p<0.0001); feeling shame for having the disease (p=0.014); absence of partners (p=0.026); and depression (p=0.004). The tendency to hide their disease from their employers was similar for the two groups. Conclusion. The age discrepancy between groups was an important limiting factor of this study. However, despite the limited number of participants and the age difference between the groups, there is no impediment in stating that people with epilepsy show high rates of unemployment, depression, and stigma.